An Analysis on Sino-UK Cultural Differences in Education from the Perspective of Hofstede’s Cultural Dimensions Theory (A Case Study of Are Our Kids Tough Enough?) - Zhang Wenxin; Wang Yue (Journal on Education, 2022)
Based on the Hofstede's cultural dimensions theory, the paper aims to analyze the cultural difference in education between China and the UK on a documentary Are Our Kids Tough Enough? Which was made by BBC. Comparative study method was undertaken for illustrating the date of culture dimensions difference of the UK’s and China’s. The result shows that the obvious difference lies on Collectivism and Individualism, Power distance, as well as long-time orientation and short-time orientation. The documentary was thus analyzed from these three perspectives. The conclusion was that 1) Chinese teachers wanted to utilize power to control British students, but students refused to obey them for their low power distance. 2) Many activities were held in the whole class by Chinese teachers for their collectivism, but the British students could not accept them and pursue their own right. 3) Chinese teachers took the the final exam seriously because of long-term orientation but the British students were reverse for their short-term orientation. 4) The date of uncertainty avoidance and Masculinity are almost the same in these two countries, but they were reflected in different ways. And with the conclusion, the effective strategies to overcome culture conflict will be offered to Chinese teachers and all other teachers in the cross-culture communication context.